ANALISIS ASSESMENT KOMPETENSI KETERAMPILAN MENGAJAR DALAM PERKULIAHAN MICRO TEACHING BERBASIS NILAI KEISLAMAN PADA MAHASISWA PAI - Syahrur Ramli; Silvia Susrizal; Susi Herawati; M. Ravi Akbar (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This research aims to analyze the evaluation results of micro teaching lectures for Islamic Education students using assessment indicators of teaching skills based on Islamic values. Islamic Education students are prepared to become prospective Islamic Education teachers through basic teaching skills that consist of skills in opening, explaining, questioning, providing reinforcement, variation, using media, managing the classroom, and closing the learning process. The observation results show that the Islamic Education students have not optimally implemented Islamic values in micro teaching practices. The preliminary questionnaire results with two indicators, opening and questioning skills, indicate that 70% of respondents are not skilled in using Islamic values. This research uses a mixed method approach by combining analysis of the results of a questionnaire on Islamic teaching skills, with coursework grades and interviews. The results show that the highest micro teaching skills based on Islamic values are found in the indicators